Unilateral conductive hearing loss and ADHEAR: 2 case reports - Ricardo Roleiro; Tatiana Marques; António Miguéis (Acta Oto-Laryngologica Case Reports)
Bone conduction systems are sometimes not well tolerated due to the tension on the skull. Therefore, a brand non-surgical device was developed, the ADHEAR (MED-EL, Innsbruck, Austria). It is based on a novel fixation system using an adhesive adapter, which allows for a more comfortable and efficient mechanical transmission of the acoustic signal and that can be used as treatment for conductive hearing loss. The purpose of the study is to evaluate the performance of ADHEAR in two patients with unilateral conductive hearing loss. An 8-years-old patient with external ear canal stenosis obtained a functional gain of 28.75 dB, while a 16-years-old patient with Goldenhar syndrome showed a recovery of 53.75 dB. Therefore, both cases suggest that ADHEAR appears to be an effective treatment for pediatric patients who due to the medical condition cannot be treated surgically or fitted with conventional hearing aids.